Micro regions as major criterion in the list of organs transplantation: a proposal to popular participation - Pedra, Adriano Sant'Ana; Moraes, Diego Pimenta (Journal of Health Law, 2011)
From the principle of participation, the national system of organ transplantation and the current formation of the single list of receivers, is proposed a new criterion of weight in the formulation of the single list of receivers. It is argued that the proposed criterion gives more transparency to the system of single list, close the possible donors and, finally, can sensitize the population to donate organs and tissues.